A novel mouse model to evaluate neuropeptide Y–mediated melanocyte pathology. Issue 12 (22nd June 2021) - Anderson, Zoya T.; Mehl, Julian; Corder, Katelynn M.; Dobrunz, Lynn E.; Harris, Melissa L.
Abstract: Vitiligo is an autoimmune disease characterized by depigmented patches of skin due to loss of the pigment‐producing melanocytes. No cure exists for vitiligo. The available treatments are inefficient for many patients, suggesting that universal treatment approaches may be inappropriate. Deeper understanding of the mechanistic basis for variability in vitiligo aetiologies is necessary. Genetic mutations in neuropeptide Y (NPY), a widely distributed protein, are associated with increased NPY expression and increased susceptibility for vitiligo. NPY is also upregulated in the circulation and lesional skin of some vitiligo patients. However, the contributions of NPY to melanocyte pathology are not understood, and presently there are no models with which to investigate this possibility. In this study, we employed NPY‐overexpressing mice to explore the role of NPY in melanocyte dysfunction. Our results show that NPY overexpression induces progressive hair greying (depigmentation) due to premature depletion of follicular melanocyte stem cells. Additionally, NPY transcripts and protein are elevated in the skin and melanocytes of these mice, respectively, suggesting that these effects may be mediated locally. Together, these results suggest that supraphysiological levels of NPY in the skin can induce melanocyte dysfunction, thus identifying this mouse line as a novel model to study NPY‐mediated melanocyte pathology. Abstract : Chronic elevation of neuropeptide Y (NPY) in the skin induces improper maintenance of the follicular melanocyte stem cell, resulting in premature hair graying.